ANALISIS PENGARUH KUALITAS PRODUK, PERSONAL SELLING DAN DISTRIBUSI FISIK TERHADAP KEPUASAN PELANGGAN PADA JASA PENERBIT YUDHISTIRA TASIKMALAYA - Rohayana Kohir, Tatang (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This study aims to determine the effect of product quality, personal selling and physical distribution on customer satisfaction at Yudhistira Tasikmalaya Issuing Services. It’s hoped, this research will provide advice and recommendations toward Yudhistira Tasikmalaya Issuers in order to achieve company goals. The research method used is quantitative with survey methods and descriptive explanations. The total research population was 621, but 50 respondents were sampled. The data collection technique is a questionnaire, with a Likert scale as a measurement tool. While the analysis method used is path analysis, which consists of validity test, reliability test, partial test, simultaneous test and coefficient of determination test. The results showed that product quality had a significant effect on customer satisfaction with a path coefficient of 0,403. Personal selling has a significant effect on customer satisfaction with a path coefficient of 0,432. Physical distribution has a significant effect on customer satisfaction with a path coefficient of 0,259. The results of simultaneous analysis show Product Quality (X1), Personal Selling (X2), and Physical Distribution (X3) has influence on Customer Satisfaction, amounting to 0,7438